IMPLEMENTASI PERATURAN DAERAH TENTANG PENGENDALIAN DEMAM BERDARAH DENGUE DI KOTA SEMARANG - Wiwik Trapsilowati; Aryani Pujiyanti (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
The number of dengue haemorrhagic fever (DHF)cases tend to increase and potentially dengue outbreak encourage the Semarang City Government to issue local policy was Local Regulation number 5 by 2010 on DHF control, which aims to realize coordinating DHF and integrated cooperation with various parties, including the community. The aim of this study to evaluate the implementation of local regulation number 5 of 2010 concerning Control of DHF. The evaluation method this study was qualitative method using policy analysis triangle framework covering context, content, actors and process. Context of the Local Regulation on the DHF control was a health field with the policy actors are government, community and stakeholders. The content of this regulation covers the roles, rights and obligations of each policy actor, DHF control including prevention cases and outbreak and sanctions for community and officials. Regulation implementation till 2015 reached 22.6% from 177 villages. The free number of larvae tends to decrease, but incidence rate (IR) decreases too, case fatality rate (CFR) fluctuates. Sanctions mechanisms have not yet been implemented and cross-sector and community cooperation isn’t optimal. More intensive socialization both cross-sector and community should be utilizing health surveillance officers (Gasurkes) in accordance with their respective working areas.